What lies beneath : a Laura Chambers mystery - Hetherton, J. G. (Hetherton, J. G. Laura Chambers mystery., 2022)
"Perfect for fans of Jeffery Deaver and J.A. Jance, in this thrilling second book in the series, Laura Chambers finds herself caught in a deadly web of small town secrets. Hillsborough, North Carolina is a town with a dark history that is bubbling to the surface. Twenty years ago, Laura's friend's family was slaughtered in their beds, and the sole survivor, Laura's eight-year-old friend, was whisked away to distant relatives. That was the last time Laura ever saw her best friend. Twenty years later, a woman runs onto the interstate, directly into the path of a truck, and the gruesome accident leaves behind a mangled corpse. Her very last phone call was to Laura, just before she was killed, but her face is disfigured beyond recognition. Identification seems impossible, and the victim was barefoot and in a state of undress. The only thing in her possession is an old photograph depicting Laura, Laura's father--and standing next to them, her lost friend from childhood. Laura's father passed away when she was eight, and she thought she understood why he vanished from her life in the year before he died, but the photograph and the corpse begin to cast doubt on everything she thought she knew. As the lines between fact and fiction blur, Laura digs into the history of the deceased, and her own family, determined to discover what lies beneath..."--provided by publisher.